A Link Between the 1780s Blast Furnaces at Coalbrookdale and Staveley: The Note of Mr Chas. Hornblower. (3rd July 2019) - Williams, Richard; de Haan, David
ABSTRACT: In what appears to be the divulging of trade secrets to a potential rival, a Coalbrookdale Company employee provided the lessors of the Staveley furnace in Derbyshire with an account of blast furnace practice. A hurried draft by Charles Hornblower lists in considerable detail the raw materials and their proportions for charging the furnace, transport and labour costs, and advice about building the furnace hearth. Further analysis of the note provides contemporary information about the preparation of the raw materials, their composition and quality of iron produced.